Catheter-Induced Thrombosis of the Superior Vena Cava - Elio Venturini; Lucia Becuzzi; Lucia Magni (Case Reports in Vascular Medicine)
There has been an increase in the use of central venous catheters (CVCs) in clinical practice. One of the most dangerous complications associated with their use is symptomatic or asymptomatic thrombosis (T), sometimes associated with superior vena cava (SVC) syndrome, resulting from impaired venous drainage. The right heart clots can induce an increased risk of mortality due the potential pulmonary embolism (PE). We report a case of asymptomatic 83-year-old woman in whom the thrombosis was detected after an echocardiogram. Echocardiography demonstrated a cardiac mass, and the T was confirmed by (magnetic resonance imaging) MRI. The clinical scenario, a high index of suspicion and routine use of echocardiogram in patients with CVC, can lead to a correct diagnosis, preventing dangerous complications.